Germline AGO2 mutations impair RNA interference and human neurological development - Davor Lessel; Daniela M. Zeitler; Margot R. F. Reijnders; Andriy Kazantsev; Fatemeh Hassani Nia; Alexander Bartholomäus; Victoria Martens; Astrid Bruckmann; Veronika Graus; Allyn McConkie-Rosell; Marie McDonald; Bernarda Lozic; et al. (Nature Communications, 2020)
AGO2 binds to miRNAs to repress expression of cognate target mRNAs. Here the authors report that heterozygous AGO2 mutations result in defects in neurological development and impair RNA interference.